Liberalización bilateral del comercio y capacidad productiva: evidencia de los efectos de la Alianza del Pacífico en las firmas colombianas (2020)
This paper studies the impact of the Alianza del Pacífico free trade agreement on the imports and productivity of Colombian firms by applying impact evaluation methodologies and industrial organization models.